2012
DOI: 10.1007/bf03393110
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tact Training on Stereotypic Vocalizations in Children With Autism

Abstract: This study was a systematic extension of Karmali, Greer, Nuzzulo-Gomez, Ross, and Rivera-Valdes (2005) and Ahearn, Clark, MacDonald, and Chung (2007). We investigated the effects of a tact correction procedure on stereotypic vocalizations in 4 children diagnosed with autism who ranged in age from 6 to 16 years. Participants had limited vocal verbal repertoires and were primarily dependent on prompts for the emission of appropriate vocalizations. A multiple-baseline design across participants was used. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 18 publications
0
29
0
2
Order By: Relevance
“…Anecdotally, we noted multiple instances of such behavior with Jessie and Buddy. Nevertheless, future research should evaluate how appropriate language is affected by this intervention (e.g., see Guzinski, Cihon, & Eshleman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, we noted multiple instances of such behavior with Jessie and Buddy. Nevertheless, future research should evaluate how appropriate language is affected by this intervention (e.g., see Guzinski, Cihon, & Eshleman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, we evaluated the extent to which providing consequences for engaging in stereotypy decreased Sam’s motor and vocal stereotypy. We opted to evaluate PPOC with Sam because prior studies have shown that error-correction with multiple repetitions of correct or appropriate responding can decrease stereotypy and increase appropriate toy play (e.g., Foxx & Azrin, 1973; Harris & Wolchik, 1979; Peters & Thompson, 2013) as well as increase correct responding during discrete-trial teaching (e.g., Guzinski, Cihon, & Eshleman, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Tacting is a commonly taught skill to individuals diagnosed with autism (e.g., Fentress & Lerman, 2012;Guzinski, Cihon, & Eshleman, 2012;May, Hawkins, & Dymond, 2013). Teaching tacting is important, as it can lead to better communication as well as better socialization between children with autism and their peers.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%